Fenomena Mahasiswa Sendratasik dalam Penciptaan Tari : Hubungan Kemampuan Memahami Teori dengan Aplikasi Penciptaan Tari - Ildiea Fitri; Indrayuda Indrayuda (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This research aims to analyze and reveal the ability of students and the application of class B theory of Dance Structuring & Creation of FBS UNP 2020 Dance Education Study Program in understanding dance creation theory. This type of research is qualitative research with a descriptive method. The informant for this research is a Class B Sendratasik (Dance) Education Study Program Student from FBS Padang State University and a Lecturer in the Dance Creation Course. This research instrument is the researcher himself and is assisted by supporting instruments such as stationery and cameras. Data are collected through literature study, observation, interviews, documentation. The steps of analyzing data are data collection, data presentation, data reduction and data verification. The results showed that the phenomenon of dance students in dance creation has applied theories and methods of structuring and creating dance into the dance works of Naga Sakti, Salam Baindang, and Gadis Berias. The answer from the resource person can be said to be valid if the lecturer of the dance Structuring & Creation course has provided evaluation results on the conclusion table that the researcher has made and attached, because the researcher will interpret the table above, the researcher also needs cooperation to see valid results with the lecturer who teaches the Dance Structuring & Creation course in class B of the Dance Structuring & Creation Study Program Class of 2020 FBS UNP. A mature RPS and the achievement of RPS into a course become the main thing and basic science for students.